2019
DOI: 10.1002/jcb.29361
|View full text |Cite
|
Sign up to set email alerts
|

MCM7 silencing promotes cutaneous melanoma cell autophagy and apoptosis by inactivating the AKT1/mTOR signaling pathway

Abstract: Cutaneous melanoma (CM) has become a major public health concern. Studies illustrate that minichromosome maintenance protein 7 (MCM7) participate in various diseases including skin disease. Our study aimed to study the effects of MCM7 silencing on CM cell autophagy and apoptosis by modulating the AKT threonine kinase 1 (AKT1)/mechanistic target of rapamycin kinase (mTOR) signaling pathway. Initially, microarray analysis was used to screen the CM‐related gene expression data as well as differentially expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Especially, increased expression of the regulatory subunit PIK3R2 has consistently been associated with an advanced tumor stage and enhanced metastasis formation [46]. Moreover, a link between MCM7 and the PI3K pathway has previously been reported for human melanoma [47] and esophagal squamous carcinoma [48], and an inhibitory role of the MCM7 locus on the PI3K antagonist PTEN was observed in a transgenic mouse model [49]. Likewise, depletion of mcm-7 in C. elegans also lead to reduced expression of the catalytic PI3K subunit age-1, while increasing PI3K pathway activity partially suppressed the AC invasion defect caused by mcm-7 depletion.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Especially, increased expression of the regulatory subunit PIK3R2 has consistently been associated with an advanced tumor stage and enhanced metastasis formation [46]. Moreover, a link between MCM7 and the PI3K pathway has previously been reported for human melanoma [47] and esophagal squamous carcinoma [48], and an inhibitory role of the MCM7 locus on the PI3K antagonist PTEN was observed in a transgenic mouse model [49]. Likewise, depletion of mcm-7 in C. elegans also lead to reduced expression of the catalytic PI3K subunit age-1, while increasing PI3K pathway activity partially suppressed the AC invasion defect caused by mcm-7 depletion.…”
Section: Discussionmentioning
confidence: 94%
“…However, there exists a handful of reports associating pre-RC genes with cancer progression and increased cell migration [48,[58][59][60][61]. Notably, Lau et al observed reduced migration and invasion of human medulloblastoma cells after inhibition of MCM proteins [62].…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of MCM7 can inhibit the proliferation of gastric cancer cells (46). Inhibition of MCM7 can promote autophagy and apoptosis of skin melanoma cells (47).…”
Section: Discussionmentioning
confidence: 99%
“…MCM7 was involved in oncogenic signaling pathways and was highly expressed in various tumor tissues, including melanoma. MCM7 silencing promoted autophagy and apoptosis, which inhibited the migration, viability, and invasion of tumor cells in melanoma ( 43 ). MCM7 was significantly correlated with tumorigenesis, progression, malignant conversion, and prognosis in skin squamous cell carcinoma ( 44 ).…”
Section: Discussionmentioning
confidence: 99%